1999
DOI: 10.1007/s004180050416
|View full text |Cite
|
Sign up to set email alerts
|

Tubular invaginations with caveolae and coated pits in the sinus endothelial cells of the rat spleen

Abstract: The fine structure of plasmalemmal tubular invaginations with caveolae and coated pits in the sinus endothelial cells of the rat spleen has been demonstrated by scanning and transmission electron microscopy. In addition, the three-dimensional structure of the tubular invagination has been revealed by computer-aided reconstruction. The tubular invaginations of the plasma membrane plunged into the cytoplasm everywhere from the apical, lateral, and basal surfaces of the plasma membrane. The invaginations were tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…However, TRPC1 was reported to be assembled in signaling complexes associated with caveolin-scaffolding lipid raft domains and to interact with one or more components of the complex, including IP 3 R (Lockwich et al 2000). The sinus endothelial cells have abundant caveolae containing caveolin-1, À2, and À3 (Uehara and Miyoshi 1999b, 1999c. The localization of TRPC1 in caveolae shown in this study is consistent with these results.…”
Section: Discussionsupporting
confidence: 93%
“…However, TRPC1 was reported to be assembled in signaling complexes associated with caveolin-scaffolding lipid raft domains and to interact with one or more components of the complex, including IP 3 R (Lockwich et al 2000). The sinus endothelial cells have abundant caveolae containing caveolin-1, À2, and À3 (Uehara and Miyoshi 1999b, 1999c. The localization of TRPC1 in caveolae shown in this study is consistent with these results.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, during the differentiation of primary cultured muscle cells and the development of mouse skeletal muscle in vivo, caveolin-3 was demonstrated to transiently localize in the transverse tubules (TT) with clusters of caveolae (Franzini-Armstrong 1991; Parton et al 1997). We have reported tubular invaginations with clusters of caveolae in sinus endothelial cells (Uehara and Miyoshi 1999b), and in this study we showed that the clusters of caveolae were labeled with anti-caveolin-3 and -1 antibodies. It is questionable whether or not the tubular invaginations with clusters of caveolae in sinus endothelial cells play a role similar to the TT with clusters in the skeletal muscle during its development in Ca 2+ regulation.…”
Section: Discussionmentioning
confidence: 78%
“…ATP-induced [Ca 2+ ](i) increase in sinus endothelial cells is likely to be initiated at the caveolae, the P2Y1 receptor of which is localized in the basal part of sinus endothelial cells. Although numerous caveolae are distributed throughout splenic sinus endothelial cells (Uehara and Miyoshi 1999c), P2Y1 receptor is localized in caveolae in the basal part of endothelial cells. Sinus endothelial cells are a crucial site for controlling blood cell passage through the splenic cord beneath endothelial cells.…”
Section: Discussionmentioning
confidence: 99%